The convergence of stroke and dementia - Hachinski, Vladimir (Arquivos de Neuro-Psiquiatria, 2018)
Neurological disorders account for the most Disability Adjusted Life Years (DALY's) -of the Global Burden of Disease (10%). More than half of neurological DALY's result from the combination of stroke (42%) and dementia (10%). The two pose risk for each other and share the same predisposing factors. A stroke doubles the risk of dementia. The close interactions call for convergent approaches. Stroke and dementia also converge at the microscopic level. The neurovascular unit has emerged as a key organizational structure of the brain. Involvement of any of its elements affects all the others. Thus, neurodegeneration impairs the microcirculation and disturbances of the microcirculation accelerate neurodegeneration. Evolving technologies allow “in vivo” imaging of the usual mixture of vascular and neurodegenerative pathology of the elderly that makes them prone to stroke and dementia. Since they occur together, they should be prevented together with a multimodal approach of lifestyle changes and mechanistic therapeutic targets. The two fields are also converging at the policy level. The World Stroke Organization has updated its Proclamation to include potentially preventable dementias that has been endorsed by Alzheimer Disease International, The World Federation of Neurology, the American Academy of Neurology and 20 international, regional and national organizations. Those interested in stroke and those dealing with dementia should work together where they can, differ where they must, with the common aim of preventing jointly, both stroke and dementia.
Keywords: stroke; dementia; prevention